The dramaturgy of sustainability reporting: Environmental and humanitarian responsibility context - Andajani, Andajani; Riduwan, Akhmad (Journal of Accounting and Investment, 2025)
Research aims: This study aims to explore and reveal the drama of sustainability report presentation in the context of environmental and humanitarian responsibility. The study focuses on the presentation of sustainability reports and actual actions taken by companies. Design/Methodology/Approach: This study employs a literature review, drawing on data from the sustainability report of a public company in Indonesia, online journalistic news, national television, and environmental activist websites. Data are analyzed by reflecting on Erving Goffman's concept of dramaturgy. Research findings: This study reveals a five-act drama related to the presentation of sustainability reports. Companies traverse the path to presenting an honest and responsible sustainability report through five stages that are analogous to the acts of a drama performance, namely exposition, character development, action, error, solution, and resolution. Theoretical contribution/Originality: The data in this study were analyzed by reflecting on Erving Goffman's concept of dramaturgy.Practitioner/Policy implication: The theoretical and practical implications of this study suggest that sustainability reports are a key source of stakeholder legitimacy, and therefore, stakeholder trust must be maintained through the honest and responsible presentation of sustainability reports. This study opens stakeholders' insights in conducting critical readings of sustainability reports published by companies.Research limitation/Implication: The limitations of this research lie in the data sources, which are all secondary data obtained from various media. Primary data collection was not possible because the sustainability reporting dramaturgy, the theme and focus of this research, encompasses past events the company has experienced.